Recent advances in sex identification of human skeletal remains in South Africa - Mubarak Bidmos; Victoria Gibbon; Goran Š trkalj (South African Journal of Science)
We review methods of sex estimation from human skeletal remains in South Africa within the forensic context. Sex is one of the key variables in obtaining a biological profile of the individual or population whose remains are analysed. Sex estimation based on the morphological characteristics of skeletal elements is population specific and thus the establishment of regional criteria is one of the imperatives for modern forensic anthropology. A literature review was carried out wherein the available methods of sex identification (morphological, metrical, geometric morphometrics and molecular) from South African skeletal material were critically examined. The approaches to sex estimation based on bone morphology have a long and productive history in South Africa. A number of approaches providing accurate results on the local populations have been developed. Research in molecular sex determination methods is still in its infancy in South Africa and the first innovative studies appeared only in recent years. While each of the four methods analysed is bounded by a number of constraints, they seem to complement each other and provide the best results when applied in conjunction with each other.